2021
DOI: 10.30924/mjcmi.26.2.13
|View full text |Cite
|
Sign up to set email alerts
|

An overview of science evaluation in Poland and Croatia

Abstract: Science is considered to be the driving force of society and the economy; therefore, adequate evaluation and allocation of funds are necessary for achieving this. This paper briefly presents issues of the trends in the evaluation of scientific activities in Poland and Croatia. Based on the literature review, differences in the evaluation systems of individual countries have been noted, as well as several recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Evidence is provided by the passing mentions of RE dark effects in the literature sampler used here . The third factor refers to the existing problems of evaluation tools, both quantitative [12], [13] and qualitative [3], [8], [11], [53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence is provided by the passing mentions of RE dark effects in the literature sampler used here . The third factor refers to the existing problems of evaluation tools, both quantitative [12], [13] and qualitative [3], [8], [11], [53].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the ineffective research evaluation system can be identified as the main reason for the emergence of the RE dark effects. Typically, ineffectiveness arises when research evaluation systems are not subject-area/country-specific ( [4], [16], [19], [20], [26], [32], [33], [35], [41], [42]) or are not balanced to specific public needs ( [12], [15], [19], [26], [31], [38], [42]), do not account for the available scientific infrastructure ( [3], [8], [32], [35], [46]) or place too much emphasis on quantity rather than quality ( [14], [15], [17], [19], [20], [23], [30], [31], [32], [34], [36], [37], [48]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the four world-famous international rankings, including ARWU, QS, TIMES, and USNEWS, take the research output performance to evaluate the scientific research performance of universities (ARWU, 2022; Craig, 2022; Robert & Eric, 2021; Times, 2020). The methods for evaluating the scientific research performance of universities proposed by scholars are always based on bibliometric indicators (Laengle et al, 2020; Mingers & Leydesdorff, 2015; Valzano, 2020), which is a clear trend around the world (Ciurak & Wierczyński, 2021; Coombs & Meijer, 2021). Although the evaluation strategy can help the public and funders to understand the level of university scientific research, it cannot provide information for universities to optimize such activities.…”
Section: Introductionmentioning
confidence: 99%
“…Science evaluation systems in the SEE region and the broader neighborhood also increasingly focus on internationally indexed publications (Ciurak, Mijač, and Wierczyński 2021). These databases include the Elsevier Scopus and Clarivate Web of Science databases, which will be further discussed in the next section of this paper.…”
Section: Introductionmentioning
confidence: 99%